FOREST GREENING IN THE MENCERIT FOREST AREA WEST PENGADANGAN VILLAGE PRINGGASELA EAST LOMBOK - Purnawarman Purnawarman; Syukrina Rahmawati; Isnaini Yulianita Hafi; Bukhori Muslim; Sukran Makmun (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2020)
Greening is an effort to plant trees and plants in a place that is considered to be the growth and development of these plants. Afforestation / reforestation is carried out as an effort to create a beautiful area with various environmental benefits such as maintaining the balance of the water system in nature, preventing erosion and soil erosion. These community service activities are aimed at 1. Preserving the forest environment as a source of clean water 2. Reducing air pollution, and 3. Conducting outreach to residents to care about their environment. In its implementation, this activity involves lecturers, students and the community of the Mencerit people area. Its implementation includes: (1) Socialization of reforestation and forest benefits, (2) Activities of planting tree seeds, the types of trees planted include Mahoni, Sonokeling, Terembesi, and so on.